Crosslinkable PEO-PPO-PEO-based reverse thermo-responsive gels as potentially injectable materials - Sosnik, Alejandro Dario (2002)
This paper describes the functionalization and crosslinking of PluronicRTM derivatives in aqueous solution at 37°C. Pluronic dimethacrylate was obtained by reacting native PEO-PPO-PEO triblocks with methacryloyl chloride and then crosslinking them by free radical polymerization at 37°C, using a redox system. The resulting gel and its rheological behavior were characterized by different techniques. The swelling study of the crosslinked polymer was indicative of its reverse thermo-responsive behavior, as illustrated by the almost 800% water uptake of the polymer at 37°C, as opposed to the 1600% attained by the polymer at 25°C. As expected, while the Pluronic dimethacrylate gel displayed an Ec value of 142.5 ± 29.7 kPa at 37°C, the crosslinked system attained a Young's modulus three times higher: 415.2 ± 45.7 kPa. Finally, the environmental SEM analysis revealed the porous microstructure of the crosslinked gels.